Aortocaval Fistula: A Rare Cause of Venous Hypertension and Acute Renal Failure. (30th December 2012) - Takkar, Chandandeep; Choi, Lorraine; Mastouri, Nasim; Kadambi, Pradeep V.
Abstract : Spontaneous rupture of abdominal aortic aneurysm into the inferior vena cava is rare and is associated with high mortality and morbidity. The clinical presentation can be variable and thus the diagnosis can be difficult. It can present with symptoms and signs of an abdominal emergency, venous hypertension, or systemic hypoperfusion. The traditional method of repair has been open surgery which is associated with high rate of complications. We report a case of aortocaval fistula (ACF) presenting with acute renal failure and heart failure, which was treated successfully with a novel, endovascular approach.